Assessment of Posterior Superior Alveolar Canal Anatomy Using Cone Beam Computed Tomography: A Retrospective Observational Study - Samata Parakh; Amita Aditya; Vaishnavi Sawant; Radhika Nair; Surabhi Santosh Parakh; Saloni Sameyak Sabadra (Journal of International Clinical Dental Research Organization, 2025)
Background: The posterior superior artery (PSA) is a branch of the maxillary artery that supplies the lateral wall of the maxillary sinus and its overlying membrane. It is imperative for the dentists to be aware of its presence and localize it before carrying out any surgical procedure in the region, including the implant surgery. Cone-beam computed tomography (CBCT) is popular for maxillofacial imaging owing to its superior accuracy, high contrast definition, and low radiation dose as compared to the CT and hence was considered for this study. Methodology: The present study was carried out on 100 retrieved scans of patients who had undergone a CBCT examination of the maxilla. The coronal and axial sections were studied to inspect the presence of the PSA canal, and all the measurements were done in the coronal section. Results: PSA was found to be present in 41% of the individuals. The majority of these were located intraosseously (88%) with a mean diameter of 1.36 mm on both sides. No age or gender-wise difference was noted in our study with regard to the location and diameter of the PSA. No statistically significant difference was found in the mean diameter and distance of the PSA canal from anatomic reference points on the right and left side among different age and gender groups. Conclusion: Considering the presence of PSA in a significant percentage of individuals in the studied population, its anatomical characteristics must be evaluated before any surgical procedure in the concerned region.